PENGARUH MOTIVASI DAN PELATIHAN TERHADAP KINERJA KARYAWAN PT. ASTRA INTERNASIONAL TBK PANORAMA KOTA BENGKULU - Wulan Sari, Lufita; Bahrun, Khairul (UM. Bengkulu, 2025)
This research aims to determine theeffect of work motivation and job training simultaneously or partially on employee perfomance at PT. Astra Internasional Tbk Panorama Bengkulu City. This studi used quantitative method and hypothesis testingwith data collection techniques by distributing questionnaires with a likert scale. The determination technique used a total sampling with 40 respondents. Data analysis technique used descriptive analisys and inferen tial statiscal analysisnamely : validity test and reality test, multipe regression analysis, coefficient of determination analysis (R2), hypotesis test with ttest (partially) and Ftest (simultaneously). The results of test and analysis was as follows: 1) the effect of work motivation on employee perfomace, there was a partial significant effect between the variables of work motivation on employee performance. 2) there was a partial significant effect between the variables of work training on e,ployee performace. 3) The work motivation and job training have a simultaneous effect on employee performace.Keywords : Motivation, Training, Employee Performac